2003
DOI: 10.1152/ajplung.00371.2002
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin matrix polymerization regulates small airway epithelial cell migration

Abstract: The continuous conversion of soluble fibronectin into extracellular matrix fibrils occurs through a dynamic, cell-dependent process. As the extracellular matrix is assembled, changes in the conformation of matrix proteins may expose biologically active, matricryptic sites that alter cell behavior. In this study, an in vitro model of wound healing was used to determine the role of matrix fibronectin in airway epithelial cell motility. Our findings indicate that, under basal conditions, small airway epithelial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
85
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 34 publications
4
85
0
1
Order By: Relevance
“…Hence, understanding how ECM molecules influence the deposition, stability, and organization of other ECM molecules and how these combinations of ECM molecules affect cell function is essential for understanding key aspects of cell behavior that underlie tissue morphogenesis, tissue repair, and maintenance of normal tissue function. We (32,78) and others (7,14,20,31,53) previously showed that fibronectin matrix can regulate adhesion-dependent cell growth, cell migration, and cell tension generation. In this report, we demonstrate that cells can organize and maintain a fibronectin matrix in the absence of fibrillar collagen I and that the interaction of fibronectin with collagen is critical for fibronectin-enhanced cell contractility.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Hence, understanding how ECM molecules influence the deposition, stability, and organization of other ECM molecules and how these combinations of ECM molecules affect cell function is essential for understanding key aspects of cell behavior that underlie tissue morphogenesis, tissue repair, and maintenance of normal tissue function. We (32,78) and others (7,14,20,31,53) previously showed that fibronectin matrix can regulate adhesion-dependent cell growth, cell migration, and cell tension generation. In this report, we demonstrate that cells can organize and maintain a fibronectin matrix in the absence of fibrillar collagen I and that the interaction of fibronectin with collagen is critical for fibronectin-enhanced cell contractility.…”
Section: Discussionmentioning
confidence: 91%
“…Although these initial adhesive interactions are necessary for cell spreading and migration, ECM proteins elaborated by cells and organized into a fibrillar meshwork are also critical in regulating cell migration. For example, migration of FN null MF and airway epithelial cells is stimulated by cell-dependent fibronectin matrix polymerization (31). Similarly, SMC migration was shown to be regulated by cell-derived collagen (66).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations